HYBRID MANAGEMENT FOR SPONTANEOUS ISOLATED DISSECTION OF THE COMMON ILIAC ARTERY: A CLINICAL CASE - Coelho, Andreia Pires (2018)
Introduction: Iliac artery dissection without aortic involvement is a rare entity, with most cases associated with predisposing factors such as trauma, atherosclerosis, connective tissue disorders or vigorous exercise. The best treatment is not unanimous, and depends on the acuteness and severity of symptoms. Criteria for intervention include prevention of aneurysmatic degeneration, acute limb ischemia, inguinal pain and aneurysm rupture. Recent results using endovascular technique showed comparability with open repair, but there is paucity of data concerning long term results. Methods: Relevant medical data were collected from hospital database. Results: The patient is a 65 years old male, referred to the emergency department for abdominal pain in the left lower quadrant with inguinal irradiation. No signs or symptoms of acute limb ischemia were present. He had no previous history of connective tissue disease, cardiovascular risk factors, trauma or vigorous exercise. A CTA was performed, which identified an acute common left iliac artery dissection, with no evidence of vascular compromise of the ipsilateral limb He was submitted to surgical left femoral approach and percutaneous right femoral approach and dissection exclusion with two stentgrafts. Resolution of abdominal pain occurred immediately. Imagiologic follow-up with CTA was performed 12 and 24 months later with no signs of dissection or residual stenosis. Conclusion: In this case, an hybrid procedure with femoral surgical approach was performed for access site control. The use of bilateral femoral access was useful to identify the true lumen more accurately and to accommodate a more precise stent placement assuring adequate sealing. At 24 months follow-up, the patient maintains asymptomatic with no evidence of complications in the imagiologic follow-up. No signs or symptoms suggestive of connective tissue disease developed.